Metronomic Four-Drug Regimen Has Anti-tumor Activity in Pediatric Low-Grade Glioma; The Results of a Phase II Clinical Trial - Verschuur, Arnauld; Heng-Maillard, Marie-Amélie; Dory-Lautrec, Philippe; Truillet, Romain; Jouve, Elisabeth; Chastagner, Pascal; Leblond, Pierre; Aerts, Isabelle; Honoré, Stéphane; Entz-Werle, Natasha; Sirvent, Nicolas; Gentet, Jean-Claude; et al. (Frontiers in Pharmacology, 2018)
Background: Metronomic chemotherapy is defined as the frequent administration of chemotherapy at doses below the maximal tolerated dose and with no prolonged drug-free break. Objective: To assess the anti-tumour activity and toxicity of a 4-drug metronomic regimen in relapsing/refractory pediatric brain tumours (BT) with progression-free survival (PFS) after 2 cycles as primary endpoint. Methods: Patients ≥4 to 25 years of age were included with progressing BT. Treatment consisted of an 8-week cycle of celecoxib, vinblastine, and cyclophosphamide alternating with methotrexate. Kepner and Chang two-steps model was used with 10 patients in the first stage. If stabilization was observed in ≥2 patients, 8 additional patients were recruited. Assessment was according WHO criteria with central radiology review. Results: Twenty-nine patients (27 evaluable) were included in 2 groups: ependymoma (group 1, N=8), and miscellaneous BT (group 2): 3 medulloblastoma (MB), 5 high grade glioma (HGG), 11 low grade glioma (LGG), 2 other BT. After first stage, recruitment for ependymoma was closed (one patient had stable disease (SD) for 4 months). Cohort 2 was opened for second stage since 1 HGG and 3 LGG patients had SD after 2 cycles. Recruitment was limited to LGG for the second stage and 2 partial responses (PR), 6SD and 2 progressive disease (PD) were observed after 2 cycles. Of these patients with LGG, median age was 10 years, 9 patients received vinblastine previously. Median number of cycles was 6.8 (range 1-12). Treatment was interrupted in 5 patients for grade 3/4 toxicity. Conclusions: This regimen is active in patients with LGG, even if patients had previously received vinblastine. Toxicity is acceptable.